Development of a Differentiated Learning Model Through the Sport Education Model Invasion Game at an Elementary School - Dian Saputri; Mugiyo Hartono; Heny Setyawati (Journal of Physical Education and Sports, 2026)
This research is motivated by the low quality of differentiated learning implementation in Physical Education (PJOK) lessons at the elementary school level, especially in Wonokerto District. Many teachers still use conventional learning methods, with minimal student participation and limited teaching modules less suited to local needs and contexts. This research aims to develop a differentiated learning model with a Sport Education Model (SEM) approach through invasion games. This model is designed to create an interesting, contextual learning experience and can adapt to the characteristics and potential of students. The study used the Research and Development (R&D) method with the ADDIE approach, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects comprised 112 students and 4 Physical Education and Health (PJOK) teachers. The instruments included expert validation (materials, media, and pedagogy), teacher and student response questionnaires, and affective assessment. The research results show that the differentiated learning model based on the Sports Education Model is feasible and effective for implementing Physical Education (PJOK) instruction in elementary schools. This model can increase active student engagement, create a pleasant learning environment, and adapt to the characteristics and needs of students. A differentiated learning model through Sport Education. The invasion game-based model has proven more effective than conventional learning approaches in increasing student active engagement and motivation in elementary school Physical Education (PJOK) subjects. This model received an "excellent" rating from subject matter, media, and pedagogical experts and positive feedback from students and PJOK teachers.